CHARACTERIZATION OF THE OCCURRENCE OF FRACTURES IN THE ELDERLY: AN EPIDEMIOLOGICAL STUDY IN A PUBLIC HOSPITAL - Michelle Aparecida dos Santos Toneto; Paulo Cézar Mendes; Suely Amorim de Araújo (Cogitare Enfermagem)
Objective: To find out about the main postoperative complications and the clinical outcome of elderly people after corrective fracture surgery.